How the chitosan structure can affect the adsorption of pharmaceuticals from wastewaters: An overview - Yahnis Dago-Serry; Konstantinos N. Maroulas; Athanasia K. Tolkou; Nikolaos C. Kokkinos; George Z. Kyzas (Carbohydrate Polymer Technologies and Applications, 2024)
The disposal of pharmaceutical compounds in wastewater is a significant environmental and health challenge. These drug residues can have adverse effects on aquatic ecosystems and human health. Chitosan, a natural polysaccharide derived from chitin, is promising as an effective material for adsorbing pharmaceutical waste due to its unique chemical structure containing amino and hydroxy functional groups that facilitate interactions with organic molecules in wastewater. Chitosan can adopt various structural forms, such as hydrogels, nanoparticles, beads, membranes, fibers, and aerogels, which offer opportunities to optimize its performance in adsorbing drug waste. In this review, which includes articles published in the last 5 years, the influence of chitosan's structural forms, particularly on the adsorption of pharmaceutical compounds in wastewater is explored. Furthermore, the different synthesis and fabrication methods for each chitosan form and highlight their characteristics, advantages, and specific applications, are discussed. Additionally, this review delves into the adsorption mechanisms involved in each form.